(untitled) (Vietnam Journal of Community Medicine, 2021)
A cross-sectional descriptive study of the actual situation of health human resources at Phu Tho Traditional Medicine and Rehabilitation Hospital, with the combination of quantitative and qualitative research methods, was carried out among 22 in-depth interviews. The results show that the actual situation of human resources of the Hospital: The total number of hospital staff is still much insufficient than that regulated in the Circular No.08/2007/TTLT-BYT-BNV, specifically in 2017, there was a shortage of 81 staff; in 2018 there was a shortage of 82 staff and in 2019 there was a shortage of 72 staff. The education with university level of hospital staff in 2017 accounted for 33.54%; in 2018, it accounted for 38.75% and in 2019, it accounted for 41.18%. The human resources structure in 2019 of the Hospital was that: clinical staff accounted for 55%; Subclinical and pharmaceutical staff accounted for 26%; Managerial and administrative staff accounted for 19%. Some influential factors are: Working conditions and environment: The hospital always adheres to the hospital quality criteria issued by the Ministry of Health to build and develop. The Hospital’s recruitment was still passive, bound by the regulations of all levels, so it was not proactive in building and recruiting the human resources according to the actual situation of the Hospital. The additional income level in addition to salaries and allowances of the Hospital staff is still low.